Light noble gases in 12 meteorites from the Omani desert, Australia, Mauritania, Canada, and Sweden. (25th June 2013) - Leya, I.; Ammon, K.; Cosarinsky, M.; Dalcher, N.; Gnos, E.; Hofmann, B.; Huber, L.
Abstract We measured the concentrations and isotopic compositions of He, Ne, and Ar in 14 fragments from 12 different meteorites: three carbonaceous chondrites, six L chondrites (three most likely paired), one H chondrite, one R chondrite, and one ungrouped chondrite. The data obtained for the CV3 chondrites Ramlat as Sahmah (RaS) 221 and RaS 251 support the hypothesis of exposure age peaks for CV chondrites at approximately 9 Ma and 27 Ma. The exposure age for Shişr 033 (CR chondrite) of 7.3 Ma is also indicative of a possible CR chondrite exposure age peak. The three L chondrites Jiddat al Harasis (JaH) 091, JaH 230, and JaH 296, which are most likely paired, fall together with Hallingeberg into the L chondrite exposure age peak of approximately 15 Ma. The two L chondrites Shelburne and Lake Torrens fall into the peaks at approximately 40 Ma and 5 Ma, respectively. The ages for Bassikounou (H chondrite) and RaS 201 (R chondrite) are approximately 3.5 Ma and 5.8 Ma, respectively. Six of the studied meteorites show clear evidence for 3He diffusive losses, the deficits range from approximately 17% for one Lake Torrens aliquot to approximately 45% for RaS 211. The three carbonaceous chondrites RaS 221, RaS 251, and Shişr 033 all have excess 4He, either of planetary or solar origin. However, very high 4He/20Ne ratios occur at relatively low 20Ne/22Ne ratios, which is unexpected and needs further study. The measured 40Ar ages fit well into established systematics. They are between 2.5 and 4.5 Ga for the carbonaceous chondrites, older than 3.6 Ga for the L and H chondrites, and about 2.4 Ga for the R chondrite as well as for the ungrouped chondrite. Interestingly, none of our studied L chondrites has been degassed in the 470 Ma break‐up event. Using the amount of trapped 36Ar as a proxy for noble gas contamination due to terrestrial weathering we are able to demonstrate that the samples studied here are not or only very slightly affected by terrestrial weathering (at least in terms of their noble gas budget).